ENTRY DIMENSIONS FOR PENETRATING INTERNATIONAL MARKETS CASE STUDY CONDOR FOUNDATION - SIRAT, Samia; Meriem Marwa, Allali; Ibtissam, Yousfi (The journal of contemporary issues in business and government, 2024)
Today the world is witnessing a marketing revolution, due to the shift from old methods of marketing to new systems. Because the countries today have begun to compete not only on the basis of the technology and money they possess, but on the basis of their ability to do a global marketing and open new markets based on goods, and the services it constantly provides in global markets. From this standpoint, this study aims to clarify the appropriate entry dimensions for penetrating international markets. So we tried to project the latter onto Condor Electronics, the major foundation in the Algerian markets. It has been concluded that the corporation relies on the simplest form, which is direct export, to penetrate global markets, and thus it is imperative for Condor to market products that are consistent with international standards. In addition, the organization must choose other strategic alternatives in penetrating the foreign market, as this gives it control over its marketing operations.